Upregulation of miR-340 Inhibits Tumor Growth and Mesenchymal Transition via Targeting c-MET in Glioblastoma - Lin N; Li W; Wang X; Hou S; Yu D; Zhao X; Jin C; Yao G; Yan W; You Y (Cancer Management and Research, 2020)
Ning Lin,1,* Wentao Li,2,* Xiefeng Wang,2,* Shiqiang Hou,1 Dong Yu,1 Xingyuan Zhao,1 Chunjing Jin,3 Guoquan Yao,1 Wei Yan,2 Yongping You2 1Department of Neurosurgery, Chuzhou Clinical College of Anhui Medical University, The First People’s Hospital Chuzhou, Chuzhou, People’s Republic of China; 2Department of Neurosurgery, The First Affiliated Hospital of Nanjing Medical University, Nanjing, People’s Republic of China; 3Laboratory Medicine Center, Affiliated Hospital of Nantong University, Nantong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ning LinDepartment of Neurosurgery, Chuzhou Clinical College of Anhui Medical University, The First People’s Hospital Chuzhou, Chuzhou, People’s Republic of ChinaEmail lin2007512@vip.163.comYongping YouDepartment of Neurosurgery, The First Affiliated Hospital of Nanjing Medical University, Nanjing, People’s Republic of ChinaEmail YYPL9@njmu.edu.cnBackground: Epithelial–mesenchymal Transition (EMT) is involved in various cancers including glioblastoma. Our previous study has shown that miR-340 negatively correlated with EMT process in glioblastoma.Purpose: In the present study, we aim to explore the underlying molecular mechanisms of miR-340 in EMT process of glioblastomas.Materials and Methods: Using RT-qPCR assay, we analyzed the expression of miR-340 in glioma cell lines and normal human glia (NHA) cell line. Using CCK8, Colony formation assays, transwell and Western blot assays, we investigated tumor growth and EMT process. Using luciferase reporter assay, we confirmed a target of miR-340.Results: Our results showed that miR-340 was down-regulated in glioma cell lines (U87, U251 and LN229) compared to NHA cells. MiR-340 overexpression remarkably inhibited cell proliferation and invasion as well as up-regulated E-cadherin expression and down-regulated N-cadherin, Vimentin, ZEB1, Slug and Snail expressions in U251 and LN229 cells. Further studies have confirmed c-MET as a target gene of miR-340. The EMT-inhibitory effect of miR-340 was lost after c-MET expression was restored. We also identified the antitumorigenic activity of miR-340 in vivo.Conclusion: These results demonstrated that miR-340 functioned as a tumor suppressor via targeting EMT process and could be a potential therapeutic candidate for treating glioblastomas.Keywords: miR-340, EMT, c-MET, glioblastoma